Development of the immune response in pneumonia due to Staphylococcus aureus (part 6) - О.E. Abaturov; A.О. Nikulinа (Zaslavsky O.Yu., 2017)
The article on the basis of literature data demonstrates the role of cellular reactions in the development of the immune response in pneumonia caused by Staphylococcus aureus. Тhe mechanisms of interaction of Staphylococcus aureus with mast cells, neutrophils and dendritic cells of the respiratory tract are described. A comparative characteristics of neutrophilic and macrophagal phagocytosis is given.